Effect of Al/Cr addition on microstructure and mechanical properties of Ni-rich nitinol alloys - Yufei Wei; Shiyao Chen; Yancheng Jin; Mingzong Zhang; Qin Li; Yanbin Jiang; Lei Guan; Lijun Zhang (Journal of Materials Research and Technology)
Ni-rich nitinol alloy is considered as a candidate material for next-generation aerospace bearings. However, the low hardness of the binary alloy limits its wear resistance. Alloying with other elements can generally help to solve this problem, but accurate determination of their optimal amounts is quite challenging. This study applies a high-throughput two-step diffusion couple technique to study the effect of Al/Cr addition on microstructure and mechanical properties. Ni56Ti44–Ni56Ti22Al22 and Ni56Ti44–Ni56Ti22Cr22 diffusion couples are successfully prepared, and both have multi-phase structures. An averaging statistical strategy for multi-phase structure is introduced to establish their composition-structure-mechanical properties relations efficiently. For the Ni56Ti44–Ni56Ti22Al22 diffusion couples, adding less than 5.0 at% Al suppresses the decomposition of the main strengthening phase (Ni4Ti3) and thus increases the hardness of the alloy. However, Al content exceeding 5.0 at% leads to Ni2TiAl precipitation, which degrades the alloy properties. The optimal Al addition is thus determined to be 2.8 at%. For the Ni56Ti44–Ni56Ti22Cr22 diffusion couples, adding less than 1.8 at% Cr also improves the hardness through a strengthening mechanism similar to that of Al addition. If the Cr content exceeds 1.8 %, bcc (Cr) will precipitate and reduce the wear resistance. The appropriate Cr addition is found to be 1.7 %. Furthermore, compared with NiTiCr alloy, NiTiAl alloy exhibits higher hardness and lower Young's modulus in general. This work will help to accelerate the research on designing Ni-rich nitinol alloys for high-performance aerospace bearings.